Nano silicon dioxide and preparation method thereof
By mixing the fatty acid salt solution with the silicon source dispersion, a monomer coated with silicon particles was prepared and metal ions were removed with acid regulators, the problem of agglomeration of nano-silicon dioxide during the preparation process was solved, and the uniformity of particles was achieved Dispersion and high yields.
Patent Information
- Application Number
- CN202411594746.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-10
- Publication Date
- 2025-02-18
AI Technical Summary
The existing nanosilicon dioxide is prone to agglomeration during the preparation process, and the preparation method is cumbersome and the yield is not high.
The fatty acid salt solution is mixed with the silicon source dispersion to prepare the fatty acid salt to coat the silicon particle monomer to avoid agglomeration, and then remove the metal ions with an acid regulator to form a hydrophobic coating layer, and dry and calcinate to obtain nano-silicon dioxide. .
The uniform dispersion of nano-silica particles is achieved, the preparation process is simplified, the yield is improved, and the particle size is controlled.
Smart Images

Figure CN119461396A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano materials, and specifically relates to nano silicon dioxide and a preparation method thereof. Background Art
[0002] Nanomaterials are natural or artificial materials in powdery or lumpy form composed of basic particles, one or more dimensions of which are between 1 nanometer and 100 nanometers, and the total number of which accounts for more than 50% of the total number of particles in the whole material. Nanosilicon dioxide is an important component of nanomaterials. It is an artificially synthesized amorphous white fluid powder with the characteristics of small particle size, many micropores, large specific surface area, and high surface hydroxyl content. It has important applications in the fields of rubber, plastics, coatings, cosmetics, electronic materials, and polishing materials. However, it is precisely because of its high surface hydroxyl content that it is very easy to agglomerate during the preparation and production process. In patent CN108455620A, tetraethyl orthosilicate is added to polyethylene glycol, and then polyvinyl pyrrolidone is added and ultrasonically stirred to form a pure silicon liquid, and deionized water is dripped into the pure silicon liquid, and nanosilicon dioxide is finally formed in a high-temperature reactor through reflux and distillation, but this method is too cumbersome, and the yield of the prepared silicon dioxide is not high. Therefore, it is urgent to develop a new technical means to solve the above technical problems. Summary of the invention
[0003] In order to solve the above problems, the present invention provides a nano silicon dioxide and a preparation method thereof, wherein a fatty acid salt solution is mixed with a silicon source dispersion to prepare a fatty acid salt-coated silicon-containing particle monomer, thereby avoiding agglomeration of the silicon-containing particle monomer, and then an acidic regulator is used to remove metal ions in the fatty acid salt to form a hydrophobic fatty acid-coated silicon-containing particle monomer, which is dried and calcined to obtain nano silicon dioxide. The nano silicon dioxide prepared by the present invention not only has uniform particle dispersion, but also has a simple preparation process, can be mass-produced, and has a controllable particle size.
[0004] To achieve the above technical objectives, the technical solution of the present invention is as follows:
[0005] The present invention provides a method for preparing nano silicon dioxide, comprising the following steps:
[0006] S1. The silicon source, the organic solvent and the deionized water are mixed uniformly and ultrasonically dispersed to obtain a dispersion A; the fatty acid salt and the solvent are mixed uniformly and heated to obtain a fatty acid salt solution B;
[0007] S2. The fatty acid salt solution B and the dispersion A are mixed uniformly to obtain a mixed solution C;
[0008] S3. adjusting the pH value of the mixed solution C to obtain a solution D;
[0009] S4. Dehydrating and washing the solution D to obtain a material E;
[0010] S5. Drying the material E to obtain powder G;
[0011] S6. calcining the powder G to obtain the nano silicon dioxide.
[0012] In one embodiment of the present invention, in step S1, the silicon source includes organic silicon or silica sol.
[0013] In one embodiment of the present invention, in step S1, the organic silicon solution includes one or more of tetraethyl orthosilicate, methyl orthosilicate, methyltrimethoxysilane, methyltriethoxysilane, propyltrimethoxysilane and propyltriethoxysilane; preferably tetraethyl orthosilicate.
[0014] In one embodiment of the present invention, in step S1, the silica sol is selected from one or more of acidic silica sol, neutral silica sol and alkaline silica sol; preferably neutral silica sol and alkaline silica sol; more preferably neutral silica sol.
[0015] In one embodiment of the present invention, in step S1, the particle size of the silicon-containing particle monomer in the dispersion A is 1-100 nanometers, preferably 10-100 nanometers, and more preferably 30-100 nanometers.
[0016] In one embodiment of the present invention, in step S1, the organic solvent includes one or more of ethanol, propylene glycol, isopropanol and 1,3-butanediol; preferably ethanol and isopropanol; more preferably ethanol.
[0017] In one embodiment of the present invention, in step S1, the mass ratio of the silicon source, the organic solvent and the deionized water is 1:(0.01-0.1):(1-10); preferably 1:(0.01-0.1):(1-10).
[0018] In one embodiment of the present invention, in step S1, in the fatty acid salt solution B, the fatty acid salt includes one or more of potassium palmitate, magnesium palmitate, zinc stearate, sodium stearate, magnesium stearate, magnesium myristic acid, potassium myristic acid, sodium laurate, potassium laurate, aluminum laurate and magnesium laurate; preferably magnesium palmitate and sodium stearate.
[0019] In one embodiment of the present invention, in step S1, in the fatty acid salt solution B, the solvent includes one or more of ethanol, propylene glycol, isopropanol, 1,3-butanediol and deionized water; preferably ethanol and deionized water; more preferably ethanol.
[0020] In one embodiment of the present invention, in step S1, in the fatty acid salt solution B, the mass ratio of the fatty acid salt to the solvent is 1:(1-30); preferably 1:(1-20); more preferably 1:(5-10).
[0021] In one embodiment of the present invention, in step S2, the mass ratio of the fatty acid salt in the fatty acid salt solution B to the organosilicon solution in the dispersion A is (0.1-20):100; preferably (1-10):100.
[0022] In one embodiment of the present invention, in step S3, an acidic regulator is selected to adjust the pH value of the mixed solution C, and the acidic regulator includes one or more of citric acid, hydrochloric acid, sulfuric acid, acetic acid, nitric acid and phosphoric acid; preferably hydrochloric acid and sulfuric acid; more preferably hydrochloric acid.
[0023] In one embodiment of the present invention, in step S3, the pH value of the solution D is 6-8.
[0024] In one embodiment of the present invention, in step S4, the conductivity of the material E is 10 μs / cm-100 μs / cm.
[0025] In one embodiment of the present invention, in step S5, the device used for the drying process is an oven.
[0026] In one embodiment of the present invention, in step S5, the temperature of the drying treatment is 80°C-110°C; preferably 80°C-100°C; more preferably 100°C.
[0027] In one embodiment of the present invention, in step S5, the drying time is 1-8 hours, preferably 2-5 hours, and more preferably 3 hours.
[0028] In one embodiment of the present invention, in step S6, the device used for the calcination treatment is a muffle furnace.
[0029] In one embodiment of the present invention, in step S6, the temperature of the calcination treatment is 500°C-800°C, preferably 500°C-700°C, and more preferably 500°C.
[0030] In one embodiment of the present invention, in step S6, the calcination treatment time is 1-8 hours, preferably 2-5 hours, and more preferably 5 hours.
[0031] The present invention also provides a nano-silicon dioxide obtained by the above preparation method, wherein the particle size distribution width (SPAN) value of the nano-silicon dioxide is 0-5, preferably 0-2.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The present application uses a fatty acid salt solution mixed with a silicon source dispersion to prepare a fatty acid salt-coated silicon-containing particle monomer, thereby preventing the silicon-containing particle monomer from agglomerating, and then uses an acidic regulator to remove metal ions in the fatty acid salt to form a hydrophobic fatty acid-coated silicon-containing particle monomer, which is dried and calcined to obtain nano silicon dioxide. The nano silicon dioxide prepared by the present invention not only has uniform particle dispersion, but also has a simple preparation process, can be mass-produced, and has a controllable particle size. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0036] Figure 1 This is the SEM image of the nano-silicon dioxide prepared in Example 1. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0038] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0039] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0040] The existing nano-silicon dioxide is very easy to agglomerate during the preparation and production process, and the preparation method is too complicated, and the yield of the prepared silicon dioxide is not high. The present application adopts a fatty acid salt solution and a silicon source dispersion liquid to mix to prepare a fatty acid salt-coated silicon-containing particle monomer, thereby avoiding the agglomeration of the silicon-containing particle monomer, and then uses an acidic regulator to remove the metal ions in the fatty acid salt to form a hydrophobic fatty acid-coated silicon-containing particle monomer, which is dried and calcined to obtain nano-silicon dioxide. The nano-silicon dioxide prepared by the present invention not only has uniform particle dispersion, but also has a simple preparation process, can be mass-produced, and has a controllable particle size.
[0041] In order to achieve the above technical objectives, the present invention provides a method for preparing nano silicon dioxide, comprising the following steps:
[0042] S1. The organosilicon solution, the organic solvent and the deionized water are mixed uniformly and ultrasonically dispersed to obtain a dispersion A; the fatty acid salt and the solvent are mixed uniformly and heated to obtain a fatty acid salt solution B;
[0043] S2. The fatty acid salt solution B and the dispersion A are mixed uniformly to obtain a mixed solution C;
[0044] S3. adjusting the pH value of the mixed solution C to obtain a solution D;
[0045] S4. Dehydrating and washing the solution D to obtain a material E;
[0046] S5. Drying the material E to obtain powder G;
[0047] S6. calcining the powder G to obtain the nano silicon dioxide.
[0048] In one embodiment of the present invention, in step S1, the silicon source includes organic silicon or silica sol.
[0049] In one embodiment of the present invention, in step S1, the organosilicon includes one or more of tetraethyl orthosilicate, methyl orthosilicate, methyltrimethoxysilane, methyltriethoxysilane, propyltrimethoxysilane and propyltriethoxysilane; preferably tetraethyl orthosilicate.
[0050] When the silicon source is silicone, a fatty acid salt solution is mixed with an silicone dispersion to coat the surface of the silicone material with the fatty acid salt, and then an acidic regulator is used to remove the metal ions in the fatty acid salt to form a hydrophobic fatty acid-coated silicone material. After drying and calcining, nano-silicon dioxide with uniform particle size distribution is obtained.
[0051] In one embodiment of the present invention, in step S1, the silica sol is selected from one or more of acidic silica sol, neutral silica sol and alkaline silica sol; preferably neutral silica sol and alkaline silica sol; more preferably neutral silica sol.
[0052] When the silicon source is silica sol, a fatty acid salt solution is mixed with a silica sol dispersion to prepare fatty acid salt-coated silica particles to avoid agglomeration of silica monomer particles, and then an acidic regulator is used to remove metal ions in the fatty acid salt to form hydrophobic fatty acid-coated silica monomer particles, which are then dried and calcined to remove fatty acids on the surface of the silica monomer particles, and finally nano-silica with uniform particle size distribution is obtained.
[0053] In one embodiment of the present invention, in step S1, the particle size of the silicon source is 1-100 nanometers; preferably 10-100 nanometers; more preferably 30-100 nanometers.
[0054] In one embodiment of the present invention, in step S1, the organic solvent includes one or more of ethanol, propylene glycol, isopropanol and 1,3-butanediol; preferably ethanol and isopropanol; more preferably ethanol.
[0055] In one embodiment of the present invention, in step S1, the mass ratio of the silicon source, the organic solvent and the deionized water is 1:(0.01-0.1):(1-10); preferably 1:(0.01-0.1):(1-10).
[0056] In one embodiment of the present invention, in step S1, in the fatty acid salt solution B, the fatty acid salt includes one or more of potassium palmitate, magnesium palmitate, zinc stearate, sodium stearate, magnesium stearate, magnesium myristic acid, potassium myristic acid, sodium laurate, potassium laurate, aluminum laurate and magnesium laurate; preferably magnesium palmitate and sodium stearate.
[0057] In one embodiment of the present invention, in step S1, in the fatty acid salt solution B, the solvent includes one or more of ethanol, propylene glycol, isopropanol, 1,3-butanediol and deionized water; preferably ethanol and deionized water; more preferably ethanol.
[0058] In one embodiment of the present invention, in step S1, in the fatty acid salt solution B, the mass ratio of the fatty acid salt to the solvent is 1:(1-30); preferably 1:(1-20); more preferably 1:(5-10).
[0059] In one embodiment of the present invention, in step S1, the purpose of the heating treatment is to completely dissolve the fatty acid salt in the solvent, and the temperature of the heating treatment can be 60°C-100°C.
[0060] In one embodiment of the present invention, in step S2, the mass ratio of the fatty acid salt in the fatty acid salt solution B to the organosilicon solution in the dispersion A is (0.1-20):100; preferably (1-10):100.
[0061] In one embodiment of the present invention, in step S2, the fatty acid salt solution B is evenly mixed with the dispersion A to obtain a mixed solution C of fatty acid salt-coated silicon dioxide / organic silicon particles.
[0062] In one embodiment of the present invention, in step S3, an acidic regulator is selected to adjust the pH value of the mixed solution C, and the acidic regulator includes one or more of citric acid, hydrochloric acid, sulfuric acid, acetic acid, nitric acid and phosphoric acid; preferably hydrochloric acid and sulfuric acid; more preferably hydrochloric acid. In one embodiment of the present invention, in step S3, the pH value of the solution D is 6-8.
[0063] In one embodiment of the present invention, in step S3, the addition of an acidic regulator can remove metal ions in fatty acid salts, thereby preparing a solution D of fatty acid-coated silica / organic silicon particles.
[0064] In one embodiment of the present invention, in step S4, the conductivity of the material E is 10 μs / cm-100 μs / cm.
[0065] In one embodiment of the present invention, in step S5, the device used for the drying process is an oven.
[0066] In one embodiment of the present invention, in step S5, the temperature of the drying treatment is 80°C-110°C; preferably 80°C-100°C; more preferably 100°C.
[0067] In one embodiment of the present invention, in step S5, the drying time is 1-8 hours, preferably 2-5 hours, and more preferably 3 hours.
[0068] In one embodiment of the present invention, in step S6, the device used for the calcination treatment is a muffle furnace.
[0069] In one embodiment of the present invention, in step S6, the temperature of the calcination treatment is 500°C-800°C, preferably 500°C-700°C, and more preferably 500°C.
[0070] In one embodiment of the present invention, in step S6, the calcination treatment time is 1-8 hours, preferably 2-5 hours, and more preferably 5 hours.
[0071] In one embodiment of the present invention, in step S6, the calcination treatment can remove the fatty acid coating layer on the surface of the silica / organic silicon particles in the powder G, thereby obtaining nano-silicon dioxide particles with uniform particle size distribution.
[0072] The present invention also provides a nano-silicon dioxide obtained by the above preparation method, wherein the particle size distribution width (SPAN) value of the nano-silicon dioxide is 0-5, preferably 0-2.
[0073] The present invention is further described in detail below in conjunction with specific examples and comparative examples. In the present invention, unless otherwise specified, the materials and equipment used in the examples can be purchased from the market.
[0074] Example 1
[0075] This embodiment provides a method for preparing nano silicon dioxide:
[0076] 100 g of neutral silica sol with a particle size of 30 nm, 2 g of ethanol and 200 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0077] Mix 1 g of magnesium palmitate with 5 g of ethanol, and heat to 80°C to dissolve and disperse completely to obtain a fatty acid salt solution B;
[0078] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0079] 1 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0080] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0081] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0082] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0083] Example 2
[0084] This embodiment provides a method for preparing nano silicon dioxide:
[0085] 100 g of neutral silica sol with a particle size of 30 nm, 2 g of ethanol and 200 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0086] 5 g of magnesium palmitate was mixed with 25 g of ethanol, and the mixture was heated to 80° C. to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0087] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0088] 5 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0089] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0090] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0091] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0092] Example 3
[0093] This embodiment provides a method for preparing nano silicon dioxide:
[0094] 100 g of neutral silica sol with a particle size of 30 nm, 2 g of ethanol and 200 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0095] 10 g of magnesium palmitate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0096] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0097] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0098] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0099] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0100] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0101] Example 4
[0102] This embodiment provides a method for preparing nano silicon dioxide:
[0103] 100 g of neutral silica sol with a particle size of 30 nm, 2 g of ethanol and 1000 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0104] 10 g of magnesium palmitate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0105] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0106] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0107] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0108] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0109] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0110] Example 5
[0111] This embodiment provides a method for preparing nano silicon dioxide:
[0112] 100 g of neutral silica sol with a particle size of 30 nm, 5 g of ethanol and 1000 g of deionized water were mixed evenly and ultrasonically dispersed to obtain dispersion A;
[0113] 10 g of magnesium palmitate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0114] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0115] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0116] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0117] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0118] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0119] Example 6
[0120] This embodiment provides a method for preparing nano silicon dioxide:
[0121] 100 g of neutral silica sol with a particle size of 30 nm, 10 g of ethanol and 1000 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0122] 10 g of magnesium palmitate was mixed with 100 g of ethanol, and the mixture was heated to 80° C. to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0123] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0124] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0125] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0126] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0127] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0128] Example 7
[0129] This embodiment provides a method for preparing nano silicon dioxide:
[0130] 100 g of neutral silica sol with a particle size of 30 nm, 10 g of ethanol and 1000 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0131] 10 g of magnesium palmitate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0132] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0133] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0134] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0135] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0136] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0137] Example 8
[0138] This embodiment provides a method for preparing nano silicon dioxide:
[0139] 100 g of neutral silica sol with a particle size of 30 nm, 10 g of ethanol and 1000 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0140] 10 g of sodium stearate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0141] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0142] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0143] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0144] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0145] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0146] Example 9
[0147] This embodiment provides a method for preparing nano silicon dioxide:
[0148] 100 g of neutral silica sol with a particle size of 30 nm, 10 g of ethanol and 1000 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0149] 10 g of sodium stearate was mixed with 100 g of ethanol, and after being completely dissolved and dispersed at 80°C, a fatty acid salt solution B was obtained;
[0150] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0151] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0152] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0153] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0154] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0155] Example 10
[0156] This embodiment provides a method for preparing nano silicon dioxide:
[0157] 100 g of neutral silica sol with a particle size of 30 nm, 10 g of ethanol and 1000 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0158] 10 g of magnesium palmitate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0159] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0160] Add 5 g of hydrochloric acid to the mixed solution C, adjust the pH value of the mixed solution C to 8.5, and obtain solution D;
[0161] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0162] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0163] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0164] Embodiment 11
[0165] This embodiment provides a method for preparing nano silicon dioxide:
[0166] 100 g of neutral silica sol with a particle size of 60 nm, 10 g of ethanol and 1000 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0167] 10 g of magnesium palmitate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0168] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0169] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0170] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0171] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0172] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0173] Example 12
[0174] This embodiment provides a method for preparing nano silicon dioxide:
[0175] 100 g of neutral silica sol with a particle size of 60 nm, 10 g of ethanol and 1000 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0176] 10 g of sodium stearate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0177] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0178] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0179] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0180] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0181] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0182] Example 13
[0183] This embodiment provides a method for preparing nano silicon dioxide:
[0184] 100 g of neutral silica sol with a particle size of 100 nm, 10 g of ethanol and 1000 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0185] 10 g of magnesium palmitate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0186] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0187] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0188] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0189] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0190] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0191] Embodiment 14
[0192] This embodiment provides a method for preparing nano silicon dioxide:
[0193] 100 g of neutral silica sol with a particle size of 100 nm, 10 g of ethanol and 1000 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0194] 10 g of sodium stearate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0195] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0196] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0197] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0198] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0199] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0200] Embodiment 15
[0201] This embodiment provides a method for preparing nano silicon dioxide:
[0202] 100 g of tetraethyl orthosilicate with a particle size of 100 nm, 10 g of ethanol and 1000 g of deionized water were uniformly mixed and ultrasonically dispersed to obtain a dispersion A;
[0203] 10 g of magnesium palmitate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0204] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0205] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0206] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0207] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0208] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0209] Example 16
[0210] This embodiment provides a method for preparing nano silicon dioxide:
[0211] 100 g of tetraethyl orthosilicate with a particle size of 100 nm, 10 g of ethanol and 1000 g of deionized water were uniformly mixed and ultrasonically dispersed to obtain a dispersion A;
[0212] 10 g of sodium stearate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0213] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0214] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0215] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0216] The material E was dried in an oven at 100°C for 3 hours to obtain powder G;
[0217] The powder G was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0218] Comparative Example 1
[0219] This comparative example provides a method for preparing nano silicon dioxide:
[0220] Add 10 g of ethanol, 100 g of deionized water, and 3 g of concentrated aqueous ammonia into a conical flask, and stir for 10 minutes to fully mix the concentrated aqueous ammonia with the solution to obtain dispersion A;
[0221] 100 g of neutral silica sol with a particle size of 30 nanometers and 10 g of ethanol were mixed to obtain a mixed solution B;
[0222] Add mixed solution B to dispersion solution A and stir for 30 minutes to obtain solution C;
[0223] The stopper of the conical flask was tightly closed and the reaction was carried out at room temperature for 2 h to obtain solution D;
[0224] After the reaction of solution D was completed, it was centrifuged and washed 5 times with water and ethanol respectively to obtain powder E;
[0225] The powder E was dried in a drying oven at 100° C. for 5 hours and ground to obtain nano-silicon dioxide.
[0226] Comparative Example 2
[0227] This comparative example provides a method for preparing nano-silicon dioxide. This comparative example is similar to Example 7, except that no pH regulator is added.
[0228] 100 g of neutral silica sol with a particle size of 30 nm, 10 g of ethanol and 1000 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0229] 10 g of magnesium palmitate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0230] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0231] The solution C was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain material D;
[0232] The material D was dried in an oven at 100°C for 3 hours to obtain powder E;
[0233] The powder E was calcined in a muffle furnace at 500° C. for 5 hours to obtain nano-silicon dioxide.
[0234] Comparative Example 3
[0235] This comparative example provides a method for preparing nano-silicon dioxide. This comparative example is similar to Example 7, except that no calcination is performed.
[0236] 100 g of neutral silica sol with a particle size of 30 nm, 10 g of ethanol and 1000 g of deionized water were mixed evenly and dispersed by ultrasonic to obtain dispersion A;
[0237] 10 g of magnesium palmitate was mixed with 50 g of ethanol, and the mixture was heated to 80°C to dissolve and disperse completely, thereby obtaining a fatty acid salt solution B;
[0238] The fatty acid salt solution B and the dispersion A were stirred and mixed for 1 hour to obtain a mixed solution C;
[0239] 10 g of hydrochloric acid was added to the mixed solution C to adjust the pH value of the mixed solution C to 6.5 to obtain solution D;
[0240] The solution D was dehydrated and washed with water until the conductivity was 40 μs / cm to obtain the material E;
[0241] The material E was dried in an oven at 100° C. for 3 hours to obtain nano-silicon dioxide.
[0242] Performance Testing:
[0243] The size of a particle is called particle size. Generally, the size of a particle is expressed in diameter, so it is also called particle size. Particle size is an important physical property of powders, particles or dispersed substances, and has an important impact on the performance and application of the product. Particle size distribution refers to the number or mass of particles contained in different particle size ranges. The so-called particle size distribution refers to the proportion of particles of different particle sizes in a certain particle group, also known as the dispersion of particles. Particle size distribution can effectively show the uniformity and agglomeration of particles. It can usually be expressed by D10, D20, D30, D40, D50, D60, D70, D80, D90, D97, and D100. D50 is also called the median diameter or median particle size, which accurately divides the population into two equal parts. 50% of the particles exceed this value, and 50% of the particles are lower than this value. D100 refers to the volume content of particles smaller than this particle size accounting for 100% of all particles. The particle size distribution width (SPAN) is another indicator that characterizes the width of the particles. It is usually used to characterize asymmetric distribution particle systems, especially when the particle diameter distribution shows a large deviation. The calculation formula of the particle size distribution width (SPAN) is (D90-D10) / D50. The larger the value, the wider the distribution. In the embodiment of the present invention, since the particle size used is 10 nanometers to 100 nanometers, which is a fixed value, the change in the particle size distribution width (SPAN) value indicates that the particles are agglomerated. The larger the SPAN value, the more serious the agglomeration.
[0244] Particle size distribution test: The test was conducted using the NANOPHOX nano-laser particle size analyzer from German Synpatek, which has a test range of 0.5 nm to 10000 nm. The particle size distribution test results of the nano-silicon dioxide prepared in Examples 1-16 and Comparative Examples 1-3 are shown in Table 1.
[0245] Table 1 Particle size distribution test results of nano silicon dioxide prepared in Examples 1-16 and Comparative Examples 1-3
[0246]
[0247] As shown in Table 1, from the comparison of Example 1, Example 2 and Example 3, the amount of fatty acid salt can affect the dispersion effect of final nano silicon dioxide, this is because the amount of fatty acid salt increases, can improve the coverage rate of silicon-containing particle monomer, less probability of silicon-containing particle monomer adhesion again in the last drying stage, but fatty acid salt is not easy to be too much, excessive will cause self cross-linking, make silicon-containing particle monomer agglomerate in excessive fatty acid, be unfavorable for the formation of silicon-containing particle monomer. In embodiments of the present invention, it is most suitable when the consumption of fatty acid salt is 10%Wt of silicon source.
[0248] From the comparison between Example 3 and Example 4, the amount of deionized water used in the silicon source will affect the dispersion effect of nano-silicon dioxide to a certain extent. This is because the more deionized water, the more dilute the silicon source, the larger the distance between the silicon-containing particle monomers, and the more conducive to the formation of silicon-containing particle monomers. However, since the silicon-containing particle monomers in the silicon source are limited, the more deionized water is not necessarily better. The more deionized water, the lower the yield, the higher the cost, and it is not conducive to production. In the embodiment of the present invention, when the mass ratio of the silicon source to the deionized water is 1:10, the effect is best.
[0249] From the comparison between Example 4, Example 5 and Example 7, it can be seen that the amount of solvent used in the silicon source will affect the dispersion effect of nano-silicon dioxide to a certain extent. This is because the solvent here plays a role of assisting dispersion. The dispersion effect increases with the increase of solvent, but the more solvent, the better. When the silicon-containing particle monomers in the silicon source are all dispersed, the excess solvent does not play any role, resulting in waste. In the embodiment of the present invention, the best effect is achieved when the mass ratio of the silicon source to the solvent is 1:0.1.
[0250] From the comparison between Example 6 and Example 7, and Example 8 and Example 9, it can be seen that the amount of solvent used in the fatty acid salt has no significant effect on the dispersion effect of nano-silicon dioxide.
[0251] From the comparison between Example 5 and Example 8, and Example 7 and Example 9, the particle size distribution width (SPAN) of nano-silicon dioxide prepared by selecting magnesium palmitate and sodium stearate as fatty acid salts is basically the same, indicating that the effect of using magnesium palmitate or sodium stearate to prepare nano-silicon dioxide is equivalent.
[0252] From the comparison between Example 7 and Example 10, the amount of hydrochloric acid will affect the dispersion effect of nano silicon dioxide. This is because the amount of hydrochloric acid is insufficient, the neutralization is incomplete, and the metal ions in the fatty acid salt are residual, which will cause serious agglomeration in the drying stage. Therefore, the pH needs to be adjusted to neutrality to completely separate the metal ions in the fatty acid salt. In the embodiment of the present invention, the best effect is achieved when the pH is 6.5.
[0253] From the comparison between Example 7, Example 11 and Example 13, and Example 8, Example 12 and Example 14, it can be seen that the particle size distribution width (SPAN) values of silicon sources with different particle sizes are different. The larger the particle size, the larger the value, which shows that the particle size of the silicon source will affect the degree of agglomeration to a certain extent. This is because the larger the particle size, the larger the contact area between the silicon-containing particle monomers, the higher the contact probability between the hydroxyl groups on the surface of the silicon-containing particle monomers, and the more serious the agglomeration. In the embodiment of the present invention, the best effect is to use a 30-nanometer silicon source.
[0254] From the comparison between Example 13 and Example 15, and Example 14 and Example 16, it can be seen that the particle size distribution widths of the nano-silicon dioxide prepared by using organic silicon and silica sol as the silicon source are basically the same, indicating that the effects of using organic silicon and silica sol as the silicon source to prepare nano-silicon dioxide are equivalent.
[0255] From the comparison between Example 7 and Comparative Example 1, it can be seen that the particle size distribution width (SPAN) value of the nano-silicon dioxide prepared by the conventional method for preparing nano-silicon dioxide is much larger than that of the method used in Example 7 of the present invention. This is because the conventional method cannot solve the problem of nano-silicon dioxide re-agglomeration during the drying stage.
[0256] From the comparison between Example 7 and Comparative Example 2, it can be seen that the pH adjuster is very important in the present invention. Without adjusting the pH, the particle size distribution width (SPAN) value of the prepared nano-silicon dioxide is much larger than that of Example 7. This is because, if the pH adjustment is not performed, the metal ions in the fatty acid salt will not be replaced, and the final result is silicon monomer particles coated with water-soluble fatty acid salts. During dehydration and washing, the nano-silicon dioxide cannot be completely separated from the water, and secondly, when drying after washing, it will rely on water to re-agglomerate, and the nano-silicon dioxide finally prepared is severely agglomerated.
[0257] From the comparison between Example 7 and Comparative Example 3, the particle size distribution width (SPAN) value of the nano-silica prepared without calcination is much larger than that of Example 7. This is because the nano-silica prepared without calcination has a fatty acid coating on its surface and is not the final desired nano-silica. The fatty acids are very easy to agglomerate during drying, which ultimately leads to severe agglomeration of the nano-silica prepared in Comparative Example 3.
[0258] In summary, Example 7 has the best effect, that is, when the particle size of the silicon source selected is 30 nm, the mass ratio of the silicon source, the solvent, and deionized water is 1:0.1:10, the amount of fatty acid salt is 10% Wt of the silicon source, the mass ratio of fatty acid salt to solvent is 1:5 and the pH is adjusted to 6.5, the effect is best.
[0259] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing nano silicon dioxide, characterized in that: The following steps are involved: S1. The silicon source, the organic solvent and the deionized water are mixed uniformly and ultrasonically dispersed to obtain a dispersion A; the fatty acid salt and the solvent are mixed uniformly and heated to obtain a fatty acid salt solution B; S2. The fatty acid salt solution B and the dispersion A are mixed uniformly to obtain a mixed solution C; S3. adjusting the pH value of the mixed solution C to obtain a solution D; S4. Dehydrating and washing the solution D to obtain a material E; S5. Drying the material E to obtain powder G; S6. calcining the powder G to obtain the nano silicon dioxide.
2. The preparation method according to claim 1, characterized in that: In step S1, the silicon source includes organosilicon or silica sol, the organosilicon is selected from one or more of ethyl orthosilicate, methyl orthosilicate, methyltrimethoxysilane, methyltriethoxysilane, propyltrimethoxysilane, and propyltriethoxysilane, and the silica sol is selected from one or more of acidic silica sol, neutral silica sol, and alkaline silica sol.
3. The preparation method according to claim 1, characterized in that: In step S1, the particle size of the silicon-containing particles in the dispersion A is 1-100 nanometers; and / or the organic solvent includes one or more of ethanol, propylene glycol, isopropanol and 1,3-butanediol.
4. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the silicon source, the organic solvent and the deionized water is 1:(0.01-0.1):(1-10).
5. The preparation method according to claim 1, characterized in that: In step S1, the preparation of the fatty acid salt solution B satisfies at least one of the following characteristics: (1) The fatty acid salt includes one or more of potassium palmitate, magnesium palmitate, zinc stearate, sodium stearate, magnesium stearate, magnesium myristic acid, potassium myristic acid, sodium laurate, potassium laurate, aluminum laurate and magnesium laurate; (2) The solvent includes one or more of ethanol, propylene glycol, isopropanol, 1,3-butanediol, and deionized water; (3) The mass ratio of the fatty acid salt to the solvent is 1:(1-30).
6. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the fatty acid salt in the fatty acid salt solution B to the silicon source in the dispersion A is (0.1-20):
100.
7. The preparation method according to claim 1, characterized in that: In step S3, an acidic regulator is selected to adjust the pH value of the mixed solution C, and the acidic regulator includes one or more of citric acid, hydrochloric acid, sulfuric acid, acetic acid, nitric acid and phosphoric acid; the pH value of the solution D is 6-8.
8. The preparation method according to claim 1, characterized in that: In step S4, the conductivity of the material E is 10 μs / cm-100 μs / cm.
9. The preparation method according to claim 1, characterized in that: In step S5, the drying treatment is carried out at a temperature of 80°C-110°C for a period of 1-8 hours; and / or, in step S6, the calcination treatment is carried out at a temperature of 500°C-800°C for a period of 1-8 hours.
10. A nano-silicon dioxide, characterized in that: The nano-silicon dioxide prepared by the preparation method according to any one of claims 1 to 9 has a particle size distribution width (SPAN) value of 0-5.
Citation Information
Patent Citations
Preparation method of nano silica
CN108455620A